Thalamocortical white matter connectivity and the entorhinal cortex as neural correlates of electroconvulsive therapy response in patients with schizophrenia spectrum disorder - Minah Kim; Eugenie Choe; Hyungyou Park; Silvia Kyungjin Lho; Sun-Young Moon; Sanghoon Oh; Jun Soo Kwon (Brain Stimulation)
Background: Electroconvulsive therapy (ECT) is an effective treatment for patients with treatment-resistant schizophrenia spectrum disorder (SSD); however, the underlying mechanisms of ECT remain unclear, and region-specific neuromodulation targets are not well defined. Abnormally reduced thalamo-prefrontal cortex (PFC) and increased thalamo-parietal cortex (PC) connectivity have been linked to schizophrenia pathophysiology. In this study, thalamocortical white matter (WM) connectivity was examined as a potential biomarker of ECT response, and the brain regions that mediate ECT-induced changes in SSD patients were explored. Methods: Twenty-six SSD patients and 28 age- and sex-matched healthy controls (HCs) underwent diffusion-weighted magnetic resonance imaging to assess thalamocortical WM connectivity. SSD patients were scanned twice, before (T1) and after (T2) ECT, over 1–2 months. Associations between changes in thalamocortical WM connectivity and symptom improvement were analyzed. Mediation analysis using graph theoretical analysis of structural connectomes was performed to identify modulating regions associated with WM connectivity changes. Results: At T1, SSD patients exhibited lower thalamo-lateral PFC and greater thalamo-PC WM connectivity than HCs did. At T2, the group-level difference in thalamo-PC WM connectivity disappeared. In SSD patients, thalamo-PC WM connectivity significantly decreased between T1 and T2, which was associated with symptom improvement. Mediation analysis revealed that the degree centrality of the right entorhinal cortex significantly mediated ECT-induced changes in thalamo-PC WM connectivity. Conclusion: These findings suggest that a reduction in increased thalamo-PC WM connectivity may be a biomarker for ECT response in SSD patients. Furthermore, the right entorhinal cortex may be a neuromodulation target for treatment-resistant SSD.